Kepuasan Pemustaka Terhadap Kegiatan Sosialisasi Layanan di UIN Sunan Gunung Djati Bandung - Eded Sudirman; Nailah Hanum Hanany; Robi’in Robi’in (Institut Agama Islam Negeri Salatiga, 2019)
One of the activities to attract the interest of library users, need to use the service marketing triangle which includes internal marketing, external marketing and interactive marketing. Currently, the UIN Sunan Gunung Djati Library Center is conducting socialization as part of an external marketing effort to attract service users. In terms of service dissemination activities to new students, the main target is the increased utilization of library services by students. So far there has been no measure of whether this outreach activity really reaches its goals or not. In addition, information must also be obtained from users, especially new students about what are their needs and expectations so that their interest in utilizing library services is getting higher. Research is carried out by survey methods for new students who have received service socialization. The respondents were 282 people determined by the Slovin method. Based on the results of the research, it can be concluded that socialization activities have a positive effect on the level of access of users to library services. In terms of satisfaction with socialization activities, more than 70% of respondents were satisfied and the information submitted was adequate, but respondents felt the facilities used still needed to be improved, especially the availability of internet access.